Preliminary results of study in dust air pollution level in the territory of Asinovo region (Tomsk oblast); Проблемы геологии и освоения недр; Т. 2 - Melchukova N. O. (Geology, mining and petroleum engineering (English, German), 2012)
Заглавие с титульного листа